Calibration of Water Distribution Unit in Subak Irrigation System - Gusti Ngurah Hesa Respati, I; Nurrochmad, Fatchan; Prima Ari Pratiwi, Endita (Fakultas Teknik, Universitas Brawijaya, 2026)
The Subak system has an irrigation water distribution unit known as tektek and an intake structure called Tembuku Penyahcah. The adjustment of the number of tektek in Subak Pulagan to ensure equitable water utilization within the subak is still based on estimations by the Pekaseh (Subak leader). Therefore, it is necessary to analyze the actual water distribution in the observed plots. This study aims to formulate an equation using the broad-crested weir approach for the Tembuku Penyahcah intake structure and to validate the resulting calculations. The study was conducted during the second rice planting season of 2021, from August to December, on an observation plot covering 7.70 hectares. The research stages included obtaining measured discharge data from water-level observations and flow rate measurements and performing regression analysis using the power equation. Calibration analysis was performed by comparing the discharge equation of the broad-crested weir with the measured discharge using the power equation. The exponent of the water depth (h) was adjusted to match the exponent in the broad-crested weir equation. Validation of various discharge equations against the measured discharge was conducted using correlation coefficient, RMSE, relative RMSE, MAE, and relative MAE methods. The results indicate that the calibrated discharge coefficients for the Tembuku Penyahcah intake structures A, B, C, and D are 0.500, 0.410, 0.710, and 5.233, respectively. The validation results show that the calibrated discharge curve equation effectively reduces error compared to the theoretical broad-crested weir discharge curve.